An affordable platform for automated synthesis and electrochemical characterization - Pablo-García, Sergio; García, Ángel; Akkoç, Gün Deniz; Sim, Malcolm; Cao, Yang; Somers, Maxine; Hattrick, Chance; Yoshikawa, Naruki; Dworschak, Dominik; Hao, Han; Aspuru-Guzik, Alán (Device, 2024)
Electrochemical techniques are pivotal for materials discovery and renewable energy; however, often the extensive chemical spaces to be explored require high-throughput experimentation to ensure timely results, which are costly for both instruments and materials/consumables. While self-driving laboratories (SDLs) promise efficient chemical exploration, most contemporary implementations demand significant time, economic investment, and expertise. This study introduces an open and cost-effective autonomous electrochemical setup comprising a synthesis platform and a custom-designed potentiostat device. We present an automated electrochemical module for SDLs that offers rapid deployment and extensive control over electrochemical experiments compared to commercial alternatives. Using ChemOS 2.0 for orchestration, we showcase our setup's capabilities through a campaign reacting different metal ions with ligands to form coordination compounds, yielding a database of 400 electrochemical measurements. Committed to open science, we provide the potentiostat design, campaign software, and raw data, aiming to democratize customized components in SDLs and ensure transparent data sharing and reproducibility.
CRIS-Team Scopus Importer:2024-11-08
Keywords: DTI-3: Develop

Electrospun Iridium-Based Nanofiber Catalysts for Oxygen Evolution Reaction: Influence of Calcination on Activity-Stability Relation - Kovács, Miklós; Fritsch, Birk; Lahn, Leopold; Bachmann, Julien; Kasian, Olga; Mayrhofer, Karl; Hutzler, Andreas; Dworschak, Dominik (ACS Applied Materials and Interfaces, 2024)
The enhanced utilization of noble metal catalysts through highly porous nanostructures is crucial to advancing the commercialization prospects of proton exchange membrane water electrolysis (PEMWE). In this study, hierarchically structured IrOx-based nanofiber catalyst materials for acidic water electrolysis are synthesized by electrospinning, a process known for its scalability and ease of operation. A calcination study at various temperatures from 400 to 800 °C is employed to find the best candidates for both electrocatalytic activity and stability. Morphology, structure, phase, and chemical composition are investigated using a scale-bridging approach by SEM, TEM, XRD, and XPS to shed light on the structure-function relationship of the thermally prepared nanofibers. Activity and stability are monitored by a scanning flow cell (SFC) coupled with an inductively coupled plasma mass spectrometer (ICP-MS). We evaluate the dissolution of all metals potentially incorporated into the final catalyst material throughout the synthesis pathway. Despite the opposite trend of performance and stability, the present study demonstrates that an optimum between these two aspects can be achieved at 600 °C, exhibiting values that are 1.4 and 2.4 times higher than those of the commercial reference material, respectively. The dissolution of metal contaminations such as Ni, Fe, and Cr remains minimal, exhibiting no correlation with the steps of the electrochemical protocol applied, thus exerting a negligible influence on the stability of the nanofibrous catalyst materials. This work demonstrates the scalability of electrospinning to produce nanofibers with enhanced catalyst utilization and their testing by SFC-ICP-MS. Moreover, it illustrates the influence of calcination temperature on the structure and chemical composition of the nanofibers, resulting in outstanding electrocatalytic performance and stability compared to commercial catalyst materials for PEMWE.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Acidic water electrolysis; Catalyst morphology; Electrospinning; Enhanced catalyst utilization; Iridium oxide; Temperature-controlled synthesis

Stability of Bipolar Plate Materials for Proton-Exchange Membrane Water Electrolyzers: Dissolution of Titanium and Stainless Steel in DI Water and Highly Diluted Acid - Fiedler, Lena; Ma, Tien Ching; Fritsch, Birk; Risse, Jan Henning; Lechner, Michael; Dworschak, Dominik; Merklein, Marion; Mayrhofer, Karl; Hutzler, Andreas (ChemElectroChem, 2023)
The widespread use of proton exchange membrane water electrolyzers (PEMWE) is hindered by their high cost, of which a colossal factor is caused by the bipolar plates (BPP). In this paper, we investigate the stability of two BPP materials on-line with an optimized scanning flow cell setup coupled to an inductively coupled plasma mass spectrometer (SFC-ICP-MS), as well as scanning electron microscopy (SEM). The stability of currently used titanium and a cheaper alternative, stainless steel (SS) 316L, were characterized in deionized (DI) water and 0.5 mM H2SO4 to mimic the conditions at the BPP under operation. We show that the dissolution of Ti is negligible, whereas SS 316L degrades notably. Here, besides pH, the applied potentials play a crucial role. Nonetheless, even for the highest measured dissolution rate of SS 316L, the contamination in a full cell is estimated to remain below 1 ppm. This work illustrates the capabilities of on-line high-throughput stability tests for BPP materials and could therefore contribute towards optimization of cost-effective PEMWE.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Cyclic voltammetry; Stability; Stainless Steel; Titanium; Water splitting